Pharmacogenetics: progress, pitfalls and clinical potential - Humphries, Steve (Henry Stewart Talks, 2008)
Therapeutic index, genetic variation determining codine and thiopurine metabolism, Pharmacogenetics and statin response, involvement of HMG co-reductase, Statin response in patients with FH, Anti-inflammatory effects of statins and the IL-6 gene, Pravastatin and CETP genotype, Initial studies, Pravastatin and CETP genotype, Meta-analysis results, Use of pharmacogenetics to avoid side effects, Warfarin and CYP2C9 as an example, Ethical concerns
Archived at 2021/02/25